ANALYSISOF METAL CONTENT OF Pb, Cu, AND CrIN LOKAN (Polymesoda expansa) FROM MAROK TUA AND KOTE COASTAL WATERS OF SINGKEP ISLAND LINGGA REGENCY RIAU ARCHIPELAGO PROVINCE - Islamiati, Bening; Nurrachmi, Irvina; Nedi, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was conducted on January - March 2018 in Marok Tua and Kote Coastal Waters, Pulau Singkep, Lingga Regency, Riau Archipelago Province. The purpose of this research is to know the metal content of Pb, Cu, and Cr on soft tissue in Lokan (P.expansa)based on 2 stations and 3 different sizes. In addition, to determine the status of heavy metal pollution and safe limits of consumption of lokan.The research used is dry method based on Yap et al., (2003).The results showed that the highest metal content of Pb was found at Station 2 with small size(6.9893 µg/g), the highest Cu metal content was found at Station 1 in large size(62.9547 µg/g) and the highest Cr content contained at Station 2 in large size (4,5800 µg/g).The MPI value of Marok Tua is 9.35 and in Kote is 8.69.Based on the calculation of PTWI, lokan still safe to consumed if it not exceed the safe limits of consumption for Pb, Cu, and Cr metal in Marok Tua (1.4842 kg/week; 18.5391 kg/week; and 1.9645 kg/week) and at Kote for Pb, Cu, and Cr metals (1.1960 kg/week; 37.0850 kg/week; and 1.5154 kg/week). Key Words : Marok Tua, Kote, Heavy Metal, Lokan (Polymesoda expansa)